Pycnodysostosis: a case series of eight Saudi patients with cathepsin K gene mutation and a literature review - Alsagheir, Afaf; Alhuthil, Raghad; Alissa, Ahmad T.; Joueidi, Faisal; Sayed, Ahmed G.; Al-Amoudi, Waleed; Alabdulhadi, Alanoud S.; Bin-Abbas, Bassam (Frontiers in Endocrinology, 2025)
Pycnodysostosis, a rare osteopetrosis subtype, is mainly caused by homozygous or compound heterozygous biallelic pathogenic mutation of the cathepsin K (CTSK) gene. The cohort included eight patients (four males and four females) with a mean current age of 13 years (SD ± 3.6) and a mean age at diagnosis of 5 years (SD ± 2). All patients had a positive family history of pycnodysostosis and were born to consanguineous parents. Genetic analysis revealed that all individuals carried the same mutation: NM_000396.3(CTSK):c.244-29A>G. Clinically, they exhibited characteristic craniofacial features and skeletal deformities consistent with the diagnosis. Bone fractures were reported in 7 out of 8 patients, highlighting a significant clinical burden. All affected individuals received growth hormone therapy(GHT), though response to treatment varied among the group. These findings emphasize the importance of early genetic screening, particularly in families with a known history of pycnodysostosis, to enable timely diagnosis and intervention. Although pycnodysostosis is typically described as a nonprogressive skeletal dysplasia, the presence of complications such as osteomyelitis and recurrent fractures may contribute to a more complex and progressive clinical course in some patients.